Chemical Signals in Vertebrates 14 2019
DOI: 10.1007/978-3-030-17616-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Smell of Disease and Injury: Scoping Evolutionary and Ecological Implications

Abstract: By the sense of smell we can recognize the peculiar perspiration of many diseases, which has an important bearing on their identification." Sushruta Samhita (an ancient Sanskrit text on medicine and surgery c. 6 th Century BCE) Puss, vomit, diarrhoea, blood, rank perspiration and halitosis-all terms that evoke repugnance amongst us due to their association with pain, disease and failing health; and all conditions linked

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…The interpretation of those studies was that males infected with the fungus engaged in terminal investment, emitting more pheromones at the cost of reduced survival (e.g., Reyes‐Ramírez, Reyes‐Ramírez, et al., 2019; Reyes‐Ramírez, Rocha‐Ortega, et al., 2019). As for our current results, only few studies have found that females may not use odor cues to determine the condition of males (Newman & Buesching, 2019; Wyatt, 2017). In other respects, infected males copulate for longer than healthy males.…”
Section: Discussionsupporting
confidence: 72%
“…The interpretation of those studies was that males infected with the fungus engaged in terminal investment, emitting more pheromones at the cost of reduced survival (e.g., Reyes‐Ramírez, Reyes‐Ramírez, et al., 2019; Reyes‐Ramírez, Rocha‐Ortega, et al., 2019). As for our current results, only few studies have found that females may not use odor cues to determine the condition of males (Newman & Buesching, 2019; Wyatt, 2017). In other respects, infected males copulate for longer than healthy males.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies on other mammals have revealed avoidance of infected conspecifics [8] and faeces [18,66], but it remained unclear whether animals avoid spatial hotspots of transmission themselves, and whether these could have population-level consequences [21,22]. Badgers respond to social scent cues and may use these to detect and avoid infested or infectious individuals [67]; furthermore, they move between setts regularly to avoid accumulating parasites [64,68], abandoning highly infested setts and chambers [49]; we posit that this behaviour has emergent population-level consequences. Wytham badgers preferentially establish their setts on northwest-facing slopes in areas with sandy soils [46], and variation in internal sett temperature and humidity are associated with reproductive success [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Various levels of social information can be conveyed through body odors, including individuality (Hold and Schleidt, 1977;Mallet and Schaal, 1998;Platek et al, 2001;Lenochova and Havlicek, 2008), self (Hold and Schleidt, 1977;Lord and Kasprzak, 1989;Mallet and Schaal, 1998;Platek et al, 2001), kin (Porter and Moore, 1981;Porter et al, 1983Porter et al, , 1985Porter et al, , 1986Porter, 1998;Schaal and Marlier, 1998;Weisfeld et al, 2003;Lundström et al, 2009;Schäfer et al, 2020), age (Haze et al, 2001;Yamazaki et al, 2010;Mitro et al, 2012), sex (Russell, 1976;Doty et al, 1978;Schleidt, 1980), andpersonality (McBurney et al, 1976;Sorokowska et al, 2012Sorokowska et al, , 2016Sorokowska, 2013a,b). Body odor can also inform about transient states such as illness (Moshkin et al, 2012;Olsson et al, 2014;Newman and Buesching, 2019), and emotions (e.g., Haviland-Jones, 1999, 2000;Prehn et al, 2006;de Groot et al, 2012de Groot et al, , 2020Zheng et al, 2018; for reviews, see Pause, 2012;Calvi et al, 2020;Kontaris et al, 2020). Beyond the mere consideration of the ability of...…”
Section: The Social Nosementioning
confidence: 99%